Local Immune Changes in Early Stages of Inflammation and Carcinogenesis Correlate with the Collagen Scaffold Changes of the Colon Mucosa - Čaja, Fabián; Stakheev, Dmitry; Chernyavskiy, Oleksandr; Kubinová, Lucie; Křížan, Jiří; Dvořák, Jiří; Rossmann, Pavel; Štěpánková, Renata; Makovický, Peter; Makovický, Pavol; Vymetalková, Veronika; Souček, Pavel; et al. (Cancers, 2021)
Continuous activation of the immune system inside a tissue can lead to remodelling of the tissue structure and creation of a specific microenvironment, such as during the tumour development. Chronic inflammation is a central player in stimulating changes that alter the tissue stroma and can lead to fibrotic evolution. In the colon mucosa, regulatory mechanisms, including TGF-β1, avoid damaging inflammation in front of the continuous challenge by the intestinal microbiome. Inducing either DSS colitis or AOM colorectal carcinogenesis in AVN-Wistar rats, we evaluated at one month after the end of each treatment whether immunological changes and remodelling of the collagen scaffold were already in development. At this time point, we found in both models a general downregulation of pro-inflammatory cytokines and even of TGF-β1, but not of IL-6. Moreover, we demonstrated by multi-photon microscopy the simultaneously presence of pro-fibrotic remodelling of the collagen scaffold, with measurable changes in comparison to the control mucosa. The scaffold was significantly modified depending on the type of induced stimulation. These results suggest that at one month after the end of the DSS or AOM inductions, a smouldering inflammation is present in both induced conditions, since the pro-inflammatory cytokines still exceed, in proportion, the local homeostatic regulation of which TGF-β1 is a part (inflammatory threshold). Such an inflammation appears sufficient to sustain remodelling of the collagen scaffold that may be taken as a possible pathological marker for revealing pre-neoplastic inflammation.
Keywords: DSS-induced colitis; chronic inflammation; tumour niche; collagen; AOM; colorectal cancer; IL-6; tissue scaffold